Analisis turunnya pendapatan petani penyadap getah Pinus di Jorong Talago Gunuang - Nadia Lora Febricha (AL-ITTIFAQ: Jurnal Ekonomi Syariah, 2022)
The background of the problem in this research is the income earned by the pine resin tapping farmers which has decreased every year due to several factors. The type of research used in this research is field research, namely research conducted in the field with farmers tapping pine resin using purposive sampling method which conducts in-depth interviews with farmers tapping pine resin as resource persons. The purpose of this study was to analyze the factors causing the decline in the income of farmers tapping pine resin in Jorong Talago Gunuang. The results of this study indicate that the factors that cause a decrease in the income of pine resin tapping farmers are the decrease in the production of sap produced by pine resin tapping farmers, which is caused by several factors, namely: 1. Limited Land Area, 2. Lack of Labor , 3. Weather, 4. Abortion, 5. Drugs or Stimulant Liquids.Keywords: Factors Causing Decreased Income, Farmers, Pine Trees